Avaliação do potencial tóxico de águas oriundas de irrigação agrícola no Baixo-Açu/RN: um problema socioambiental - Santos, Mycarla Nely Rodrigues dos (2013)
For many decades the problematic raised about the indiscriminate use of pesticides in modern agriculture has incited the interest of many researchers to discover the effects caused by such products in the environment and consequently in the life of the ones which use that products (farmers) and those people who live in places next to the agricultural areas. Facing these facts, this research had the intention of comprehend the environmental perception of habitants of the Distrito Irrigado do Baixo-Açu (DIBA), located in the semiarid of Rio Grande do Norte, by using agro toxics and its possible environmental effects, as well as evaluate the levels of toxicity of waters from agricultural runoff in this region by using eco-toxicological exams with Ceriodaphnia silvestii. Were done 86 interviews with dwellers and farmers from DIBA. With the results reached in the evaluation of the interviews it was possible to identify that one of major problems is the inappropriate discard of empty packs of the pesticides used at that place. The samples collected for eco-toxicological evaluation showed a variation in its toxicity, once that the point of collect which receives waters from different cultures presented in four out of five samples toxicity for the tested species. Therefore, it concludes that the indiscriminate use of pesticides agricultural practice presented a potential to pollute to the irrigation waters, and the absence of elucidation by the farmers about the manipulation of these products contribute to the risk of environmental contamination and the possible decrease of the quality of life of the dwellers of the region